Preparation method of rubber for air spring bag skin

By blending neoprene, epoxidized natural rubber and styrene butadiene rubber in proportion and combining appropriate additives and process, rubber materials with good air tightness, good weather resistance and excellent durability are prepared, which solves the shortcomings of existing air spring bladder rubber materials in terms of air tightness, weather resistance and durability, and significantly extends the service life of the air spring.

CN119529400AActive Publication Date: 2025-02-28NINGBO TUOPU GROUP CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202510104318.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-02-28
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The existing natural rubber materials used in air spring bladders have shortcomings in air tightness, weather resistance and durable fatigue, resulting in a shorter service life of air springs.

Method used

Neoprene, epoxidized natural rubber and styrene butadiene rubber are blended in proportion, and combined with homogenizer, high-active magnesium oxide, polyethylene wax, processing aids, plasticizers, adhesives, anti-aging agents, reinforcement fillers, zinc oxide, accelerators, vulcanizing agents and rubber anti-coke agents, rubber materials with good airtightness, good weather resistance, and excellent durability and fatigue resistance are prepared through refining and vulcanization processes.

Benefits of technology

It significantly improves the air tightness, weather resistance and durable fatigue of the air spring bladder rubber, and extends the service life of the air spring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of rubber for an air spring bag skin, which is characterized by comprising the following steps: carrying out master batch by using an internal mixer to obtain a master batch rubber sheet, standing at room temperature for 8 hours, carrying out final mixing by using the internal mixer to obtain a final mixing rubber sheet, standing at room temperature for 4 hours after discharging the rubber sheet, calendaring, and matching with a calendaring cord fabric to form a capsule, and finally, putting the capsule into a vulcanization mold, and vulcanizing to obtain the required rubber. The preparation method has the advantages that the rubber material with good air tightness, good weather resistance, excellent durability and fatigue resistance and low temperature resistance can be prepared through the method, and the rubber material can be used for preparing a bag skin of an air spring on a new energy automobile; the problem that the service life of an air spring is shortened due to early fatigue failure of air spring bag rubber used for preparing a new energy vehicle at present is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing rubber, in particular to a method for preparing rubber for air spring bag skin. Background Art

[0002] With the guidance of green environmental protection policies of the automobile industry in various countries around the world, major automobile manufacturers at home and abroad are developing new energy vehicles, mainly electric vehicles, more and more rapidly. Since new energy vehicles do not have fuel engines and the cockpit is quieter, the noise, vibration and harshness (NVH) of new energy vehicles has become the most important evaluation indicator for vehicle research and development.

[0003] As an important shock-absorbing component of new energy vehicles, air spring suspension is used to significantly improve driving comfort. The air spring bladder is an indispensable component of automobile air spring suspension. It is fastened to the upper and lower end cover connectors of the air spring to form a closed chamber. The air spring's shock-absorbing effect is achieved by filling and deflating the closed chamber. The bladder is a rubber elastomer with a cord fabric structure. It is a consumable and vulnerable part. The performance of the bladder directly determines the performance of the entire air spring. Therefore, when designing, in addition to paying attention to its appearance and size, it is also necessary to pay attention to its air tightness, low temperature resistance, explosion resistance, fatigue characteristics and other properties. At present, the rubber used to manufacture the bladder of air springs on the market mainly uses natural rubber as the main raw material. Natural rubber is a non-polar rubber with a high degree of unsaturation. It is very easy to age during long-term outdoor use. Therefore, the rubber used to make the bladder of air springs with natural rubber as the main raw material has begun to be difficult to meet the use requirements in terms of air tightness, weather resistance, and durable fatigue resistance. There is a problem of early fatigue failure of the bladder, which shortens the life of the air spring. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing rubber for air spring bladders. Through the preparation method, a rubber material with good air tightness, good weather resistance, excellent fatigue resistance and low temperature resistance can be obtained. The rubber material can be used to manufacture the bladders of air springs on new energy vehicles to increase the service life of the air springs.

[0005] The technical solution adopted by the present invention to solve the above technical problems is: A method for preparing rubber for air spring bladder skin comprises the following steps: (1) Master batching in an internal mixer: first, put 60-80 parts by weight of chloroprene rubber, 33-17 parts by weight of epoxidized natural rubber and 7-3 parts by weight of styrene-butadiene rubber into an internal mixer, lower the top plug of the internal mixer to mix; after mixing for 60 seconds, raise the top plug, add 3-5 parts by weight of magnesium oxide, 0.5-1.5 parts by weight of stearic acid, 3-5 parts by weight of homogenizing agent, 4-6 parts by weight of antioxidant, 1 -2 parts by mass of protective wax, 1-3 parts by mass of polyethylene wax, 1-2 parts by mass of processing aid and 35-55 parts by mass of reinforcing filler, lower the top plug and continue mixing; after mixing for 15 seconds, raise the top plug, add 6-10 parts by mass of plasticizer, lower the top plug and continue mixing; when the mixing temperature reaches 115°C, raise the top plug for 15 seconds, then lower the top plug and mix to 125°C and discharge the glue to obtain a masterbatch rubber sheet; (2) leaving the masterbatch film at room temperature for 8 hours; (3) Final mixing in an internal mixer: the master batch rubber sheet which has been left at room temperature for 8 hours is put into an internal mixer together with 4-6 parts by weight of zinc oxide, 0.5-1.5 parts by weight of an antioxidant, 4-6 parts by weight of an adhesive, 0.4-0.8 parts by weight of a vulcanizing agent, 2.5-3.5 parts by weight of an accelerator, and 0.2-0.4 parts by weight of a scorch retarder, and the upper top bolt is lowered for mixing. When the mixing temperature reaches 90°C, the upper top bolt is raised for 30 seconds, and then the upper top bolt is lowered for mixing and mixing to 100°C, and the rubber is discharged to obtain a final mixed rubber sheet; (4) The final refined rubber sheet obtained above is discharged on a two-roll mill and left at room temperature for 4 hours; (5) The final refined rubber sheet after being left at room temperature for 4 hours is calendered into a rubber sheet of a set thickness by a calendering machine, and a calendering cord fabric of a corresponding thickness is added to form a capsule; (6) Place the capsule obtained in the above step into a mold, close the mold and vulcanize for 10-15 minutes at a vulcanization temperature of 150-170°C to obtain the desired rubber.

[0006] The chloroprene rubber used in step (1) is DCR 40A chloroprene rubber, produced by Nippon Electric Chemical Co., Ltd. This brand of chloroprene rubber is a sulfur-adjusted type, and has excellent physical and mechanical properties, viscosity and excellent dynamic flexural resistance.

[0007] The epoxidized natural rubber used in step (1) is ENR 25 epoxidized natural rubber produced by Mitsui Chemicals Co., Ltd. The epoxidized natural rubber has good air tightness, good compatibility with chloroprene rubber, high bonding strength and good low temperature resistance.

[0008] The styrene-butadiene rubber used in step (1) is SBR 1502 synthetic rubber, produced by Qilu Branch of Sinopec. This synthetic rubber has good heat resistance and wear resistance, and a small amount of addition can improve the operability of the rubber calendering process.

[0009] The magnesium oxide used in step (1) is highly active magnesium oxide RS-180, produced by Shanxi Yuncheng Yunsheng Chemical Co., Ltd. It participates in double bond reaction in chloroprene rubber to form a cross-linked structure, so that cross-linking occurs between rubber molecules, thereby increasing the hardness and strength of the rubber, and also improving the anti-scorch performance of the rubber.

[0010] The stearic acid used in step (1) is SA1850 stearic acid, produced by Hangzhou Zanyu Oil Technology Co., Ltd. It can improve the activity of the accelerator by reacting with metal oxides and is the main vulcanization accelerator.

[0011] The homogenizing agent used in step (1) is 40MSF uniform viscosity enhancer, produced by STRUKTOL COMPANY of Germany. The homogenizing agent can significantly improve the uniformity of mixing between elastic polymers of different polarities and viscosities, thereby improving the uniformity of mixing.

[0012] The antioxidant used in step (1) is a combination of OCTAMINE antioxidant and DTPD antioxidant, wherein OCTAMINE antioxidant is produced by SI Group and DTPD antioxidant is produced by Yichang Xingchun Chemical Co., Ltd. OCTAMINE antioxidant is a particularly excellent antioxidant that can effectively improve the high temperature resistance, outdoor oxidation resistance and bending fatigue aging resistance of chloroprene rubber; the antioxidant DTPD can react with free radicals in the rubber molecular chain, thereby preventing the oxidation reaction caused by the free radicals. The combined use of the two has a synergistic effect, ensuring that the heat resistance and weather resistance of the prepared rubber are effective for a long time and extending the flexural fatigue life.

[0013] The protective wax used in step (1) is Antilux 654 microcrystalline wax, produced by Rhein Chemie (Qingdao) Co., Ltd. It can effectively prevent cracking on the rubber surface caused by the influence of ozone and weather.

[0014] The polyethylene wax used in step (1) is BN-200 polyethylene wax produced by BOUNI CHEMICAL CO., LTD. It can prevent roller sticking and improve the operability of the rubber calendering process.

[0015] The processing aid used in step (1) is Haftolat / P, produced by KETTLITZCOMPANY of Germany. It can significantly reduce the mixing temperature of the rubber and avoid the scorching tendency of sensitive rubber, especially chloroprene rubber.

[0016] The reinforcing filler used in step (1) is a combination of VN3 white carbon black and N550 carbon black, wherein VN3 white carbon black is produced by Evonik Industries AG of Germany, and N550 carbon black is produced by Cabot (Tianjin) Chemical Co., Ltd. VN3 white carbon black can provide rubber with higher tensile strength, tear strength and abrasion resistance; N550 carbon black has good processability, medium reinforcement, good elasticity and recovery, and the combination of the two can make the rubber have better tear resistance and fatigue resistance.

[0017] The plasticizer used in step (1) is Mediaplast PM plasticizer, produced by KETTLITZCOMPANY of Germany. It has excellent compatibility with chloroprene rubber and can make the chloroprene rubber products after vulcanization have excellent low-temperature flexibility.

[0018] The zinc oxide used in step (3) is an indirect process zinc oxide with a high content of more than 99.7%, which is produced by Jinhua Zinc Oxide Factory in Hanshan County, Anhui Province.

[0019] The antioxidant used in step (3) is antioxidant ZMTI, produced by RT Vanderbilt Company, Inc. The antioxidant has a significant anti-heat aging effect and has a synergistic effect when used together with an amine antioxidant, and is used to improve the heat-oxidative aging resistance.

[0020] The adhesive used in step (3) is a combination of SCCTACK TR-1102 tackifying resin and SCCTACK ST-6000 phenolic tackifying resin, produced by SCC RUBBER CHEMICAL. SCCTACK TR-1102 tackifying resin is used to promote uniform mixing between rubbers of different viscosities or polarities, and helps to evenly disperse the filler in the rubber; SCCTACK ST-6000 phenolic tackifying resin gives the mixed rubber a high viscosity, which is beneficial to the molding and bonding of the rubber and reduces the air residue between the rubber layers.

[0021] The vulcanizing agent used in step (3) is insoluble sulfur IS60-75, produced by Ningbo Aikemu New Materials Co., Ltd. The use of this vulcanizing agent can effectively avoid the problem of frosting of the adhesive layer.

[0022] The accelerator used in step (3) is a combination of N-cyclohexyl-2-benzothiazole sulfenamide and diethyl diphenyl thiuram disulfide, which is produced by Ningbo Aikemu New Materials Co., Ltd. N-cyclohexyl-2-benzothiazole sulfenamide is a late-effect high-speed vulcanization accelerator, and diethyl diphenyl thiuram disulfide is an ultra-fast accelerator with a long scorch time. The combination of the two can ensure sufficient rubber cross-linking reaction and give the vulcanized rubber the characteristics of high mechanical strength, low compression permanent deformation, and good dynamic fatigue performance.

[0023] The anti-scorching agent used in step (3) is anti-scorching agent CTP, which is produced by Shandong Yanggu Huatai Chemical Co., Ltd. The use of such an anti-scorching agent can improve the storage stability of the rubber compound.

[0024] Compared with the prior art, the invention has the following advantages: the method adopts chloroprene rubber, epoxidized natural rubber and styrene-butadiene rubber to be blended in proportion as a matrix, wherein: the chloroprene rubber has excellent physical and mechanical properties, good viscosity, and excellent dynamic flexural resistance; the epoxidized natural rubber has good air tightness, good compatibility with the chloroprene rubber, high bonding strength, and good low-temperature resistance; the styrene-butadiene rubber has good heat resistance and wear resistance, and a small amount of addition can improve the operability of the rubber calendering process; the three are blended and matched in proportion with a homogenizing agent, high-activity magnesium oxide, polyethylene wax, processing aid, plasticizer, adhesive, stearic acid, protective wax, antioxidant, reinforcing filler, zinc oxide, accelerator, vulcanizer and rubber anti-scorch agent, so as to prepare a rubber material with good air tightness, good weather resistance, excellent fatigue resistance and good low-temperature resistance, and the rubber material can be used to prepare the bladder skin of the air spring on the new energy vehicle, so as to solve the problem that the fatigue early failure of the rubber used to prepare the bladder skin of the air spring on the new energy vehicle currently leads to the shortening of the life of the air spring. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below with reference to the embodiments.

[0026] Embodiment 1: A method for preparing rubber for air spring bladder skin, comprising the following steps: (1) Master batching in an internal mixer: first, 60 parts by weight of DCR 40A chloroprene rubber, 33 parts by weight of ENR 25 epoxidized natural rubber and 7 parts by weight of SBR1502 styrene-butadiene rubber were put into an internal mixer, and the upper plug of the internal mixer was lowered for mixing; after mixing for 60 seconds, the upper plug was raised, and 3 parts by weight of high-activity magnesium oxide, 0.5 parts by weight of stearic acid, 3 parts by weight of 40MSF homogenizing agent, 1.5 parts by weight of OCTAMINE antioxidant and 2.5 parts by weight of DTPD antioxidant, 1 part by weight of 654 microcrystalline wax, 1 part by weight of BN-200 polyethylene wax, 1 part by weight of Haftolat / P processing aid, 5 parts by weight of VN3 white carbon black and 30 parts by weight of N550 carbon black were added, and the upper plug was lowered for further mixing; after mixing for 15 seconds, the upper plug was raised, and 6 parts by weight of Mediaplast PM plasticizer, lower the top plug and continue mixing; when the mixing temperature reaches 115℃, raise the top plug for 15 seconds, then lower the top plug and mix to 125℃ and discharge the glue to obtain the masterbatch rubber sheet; (2) leaving the masterbatch film at room temperature for 8 hours; (3) Final mixing in an internal mixer: the master batch rubber sheet which had been left at room temperature for 8 hours was put into an internal mixer together with 4 parts by mass of zinc oxide, 0.5 parts by mass of ZMTI antioxidant, 2 parts by mass of SCCTACK TR-1102 tackifying resin and 2 parts by mass of SCCTACK ST-6000 phenolic tackifying resin, 0.4 parts by mass of insoluble sulfur IS60-75, 1.5 parts by mass of N-cyclohexyl-2-benzothiazole sulfenamide accelerator and 1 part by mass of diethyl diphenyl thiuram disulfide accelerator, and 0.2 parts by mass of CTP scorch retarder, and the upper top bolt was lowered for mixing. When the mixing temperature reached 90°C, the upper top bolt was raised for 30 seconds, and then the upper top bolt was lowered for mixing to 100°C and the rubber was discharged to obtain a final mixed rubber sheet; (4) The final refined rubber sheet obtained above is discharged on a two-roll mill and left at room temperature for 4 hours; (5) The final refined rubber sheet after being left at room temperature for 4 hours is calendered into a 0.6 mm thick rubber sheet by a calendering machine, and is matched with a calendering cord fabric of model PA66 840D / 1 and thickness of 0.7 mm to form a capsule; (6) Place the capsule obtained in the above step into a mold, close the mold and vulcanize at a vulcanization temperature of 150°C for 15 minutes to obtain the desired rubber.

[0027] Embodiment 2: A method for preparing rubber for air spring bag skin, comprising the following steps: (1) Master batching in an internal mixer: First, 70 parts by weight of DCR 40A chloroprene rubber, 25 parts by weight of ENR 25 epoxidized natural rubber and 5 parts by weight of SBR1502 styrene-butadiene rubber were put into an internal mixer, and the upper plug of the internal mixer was lowered for mixing; after mixing for 60 seconds, the upper plug was raised, and 4 parts by weight of high-activity magnesium oxide, 1 part by weight of stearic acid, 4 parts by weight of 40MSF homogenizing agent, 2 parts by weight of OCTAMINE antioxidant and 3 parts by weight of DTPD antioxidant, 1.5 parts by weight of 654 microcrystalline wax, 2 parts by weight of BN-200 polyethylene wax, 1.5 parts by weight of Haftolat / P processing aid, 10 parts by weight of VN3 white carbon black and 35 parts by weight of N550 carbon black were added, and the upper plug was lowered for further mixing; after mixing for 15 seconds, the upper plug was raised, and 8 parts by weight of Mediaplast PM plasticizer, lower the top plug and continue mixing; when the mixing temperature reaches 115℃, raise the top plug for 15 seconds, then lower the top plug and mix to 125℃ and discharge the glue to obtain the masterbatch rubber sheet; (2) leaving the masterbatch film at room temperature for 8 hours; (3) Final refining in an internal mixer: the master batch rubber sheet which had been left at room temperature for 8 hours was put into an internal mixer together with 5 parts by mass of zinc oxide, 1 part by mass of ZMTI antioxidant, 2.5 parts by mass of SCCTACK TR-1102 tackifying resin and 2.5 parts by mass of SCCTACK ST-6000 phenolic tackifying resin, 0.6 parts by mass of insoluble sulfur IS60-75, 1.8 parts by mass of N-cyclohexyl-2-benzothiazole sulfenamide accelerator and 1.2 parts by mass of diethyl diphenyl thiuram disulfide accelerator, and 0.3 parts by mass of CTP scorch retarder, and the upper top bolt was lowered for mixing. When the mixing temperature reached 90°C, the upper top bolt was raised for 30 seconds, and then the upper top bolt was lowered for mixing to 100°C and the rubber was discharged to obtain the final refining rubber sheet; (4) The final refined rubber sheet obtained above is discharged on a two-roll mill and left at room temperature for 4 hours; (5) The final refined rubber sheet after being left at room temperature for 4 hours is calendered into a 0.6 mm thick rubber sheet by a calendering machine, and is matched with a calendering cord fabric of model PA66 840D / 1 and thickness of 0.7 mm to form a capsule; (6) The capsule obtained in the above step is placed in a mold, and the mold is closed and vulcanized for 12.5 minutes at a vulcanization temperature of 160°C to obtain the desired rubber.

[0028] Embodiment 3: A method for preparing rubber for air spring bladder skin, comprising the following steps: (1) Master batching in an internal mixer: 80 parts by weight of DCR 40A chloroprene rubber, 17 parts by weight of ENR 25 epoxidized natural rubber and 3 parts by weight of SBR1502 styrene-butadiene rubber were put into an internal mixer, and the top plug of the internal mixer was lowered for mixing; after mixing for 60 seconds, the top plug was raised, and 5 parts by weight of high-activity magnesium oxide, 1.5 parts by weight of stearic acid, 5 parts by weight of 40MSF homogenizer, 2.5 parts by weight of OCTAMINE antioxidant and 3.5 parts by weight of DTPD antioxidant, 2 parts by weight of 654 microcrystalline wax, 3 parts by weight of BN-200 polyethylene wax, 2 parts by weight of Haftolat / P processing aid, 15 parts by weight of VN3 white carbon black and 40 parts by weight of N550 carbon black were added, and the top plug was lowered for further mixing; after mixing for 15 seconds, the top plug was raised, and 10 parts by weight of Mediaplast PM plasticizer, lower the top plug and continue mixing; when the mixing temperature reaches 115℃, raise the top plug for 15 seconds, then lower the top plug and mix to 125℃ and discharge the glue to obtain the masterbatch rubber sheet; (2) leaving the masterbatch film at room temperature for 8 hours; (3) Final mixing in an internal mixer: the master batch rubber sheet which had been left at room temperature for 8 hours was put into an internal mixer together with 6 parts by mass of zinc oxide, 1.5 parts by mass of ZMTI antioxidant, 3 parts by mass of SCCTACK TR-1102 tackifying resin and 3 parts by mass of SCCTACK ST-6000 phenolic tackifying resin, 0.8 parts by mass of insoluble sulfur IS60-75, 2 parts by mass of N-cyclohexyl-2-benzothiazole sulfenamide accelerator and 1.5 parts by mass of diethyl diphenyl thiuram disulfide accelerator, and 0.4 parts by mass of CTP scorch retarder, and the upper top bolt was lowered for mixing. When the mixing temperature reached 90°C, the upper top bolt was raised for 30 seconds, and then the upper top bolt was lowered for mixing to 100°C and the rubber was discharged to obtain a final mixed rubber sheet; (4) The final refined rubber sheet obtained above is discharged on a two-roll mill and left at room temperature for 4 hours; (5) The final refined rubber sheet after being left at room temperature for 4 hours is calendered into a 0.6 mm thick rubber sheet by a calendering machine, and is matched with a calendering cord fabric of model PA66 840D / 1 and thickness of 0.7 mm to form a capsule; (6) Place the capsule obtained in the above step into a mold, close the mold and vulcanize at a vulcanization temperature of 170°C for 10 minutes to obtain the desired rubber.

[0029] The performance of the conventional rubber for manufacturing air spring bladder skin and the three air spring bladder skins prepared by the above three embodiments are compared and analyzed by tensile test, air tightness, low temperature brittle temperature, bursting pressure and bench fatigue test; the tensile strength and elongation at break of the conventional rubber for manufacturing air spring bladder skin and the three air spring bladder skins prepared by the above three embodiments are tested by a universal tensile testing machine; the air tightness of the conventional rubber for manufacturing air spring bladder skin and the three air spring bladder skins prepared by the above three embodiments are tested by a helium test bench. Test; a low-temperature brittle temperature test was performed on the rubber traditionally used for manufacturing air spring bladder skins and the three rubber material parts for manufacturing air spring bladder skins prepared by the above three embodiments using a low-temperature brittle temperature test; a bursting pressure test was performed on the rubber traditionally used for manufacturing air spring bladder skins and the three assembly parts for manufacturing air spring bladder skins prepared by the above three embodiments using a bursting test bench; a bench fatigue test was performed on the rubber traditionally used for manufacturing air spring bladder skins and the three assembly parts for manufacturing air spring bladder skins prepared by the above three embodiments using an MTS bench fatigue test bench; the results shown in the following table were obtained.

[0030] Among them, air tightness test: the test temperature is 23±3℃, the test medium is a mixture of 80% air and 20% helium, the pressure is 10Bar, the test time is 45 seconds, and the evaluation standard is ≤2.8×10 -5 mbar.l / s; Low temperature brittle temperature test: according to ISO 812:2017 (E) method C test; Burst pressure test: the test temperature is 23±3℃, the test medium is water, the pressure increase rate is 5Bar / min, and the evaluation standard is >35bar; Bench fatigue test: the test load is the maximum spring load, the test temperature is -35℃, 50℃, 80℃ cycle, the test frequency is 0.4Hz, 1.5Hz, 3Hz cycle, the evaluation standard is that the pressure loss within every 24h must be less than 1Bar, there is no harmful cracks that cause airtightness problems, and the number of fatigue times is >3 million times.

[0031]

[0032] From the data in the above table, it can be seen that the rubber for preparing air spring bladders prepared by this method is slightly better than traditional bladder rubber in tensile strength, elongation at break and explosion resistance, and has a similar low-temperature brittle temperature, but has significantly improved air tightness and bench fatigue times compared with traditional bladder rubber. Therefore, the bladders prepared by this rubber can be applied to air springs to ensure the long-term effectiveness of the fatigue durability of the air springs.

Claims

1. A method for preparing rubber for air spring bag skin, characterized in that The steps include: (1) Master batching in an internal mixer: first, put 60-80 parts by weight of chloroprene rubber, 33-17 parts by weight of epoxidized natural rubber and 7-3 parts by weight of styrene-butadiene rubber into an internal mixer, lower the top plug of the internal mixer to mix; after mixing for 60 seconds, raise the top plug, add 3-5 parts by weight of magnesium oxide, 0.5-1.5 parts by weight of stearic acid, 3-5 parts by weight of homogenizing agent, 4-6 parts by weight of antioxidant, 1 -2 parts by mass of protective wax, 1-3 parts by mass of polyethylene wax, 1-2 parts by mass of processing aid and 35-55 parts by mass of reinforcing filler, lower the top plug and continue mixing; after mixing for 15 seconds, raise the top plug, add 6-10 parts by mass of plasticizer, lower the top plug and continue mixing; when the mixing temperature reaches 115°C, raise the top plug for 15 seconds, then lower the top plug and mix to 125°C and discharge the glue to obtain a masterbatch rubber sheet; (2) leaving the masterbatch film at room temperature for 8 hours; (3) Final mixing in an internal mixer: the master batch rubber sheet which has been left at room temperature for 8 hours is put into an internal mixer together with 4-6 parts by weight of zinc oxide, 0.5-1.5 parts by weight of an antioxidant, 4-6 parts by weight of an adhesive, 0.4-0.8 parts by weight of a vulcanizing agent, 2.5-3.5 parts by weight of an accelerator, and 0.2-0.4 parts by weight of a scorch retarder, and the upper top bolt is lowered for mixing. When the mixing temperature reaches 90°C, the upper top bolt is raised for 30 seconds, and then the upper top bolt is lowered for mixing and mixing to 100°C, and the rubber is discharged to obtain a final mixed rubber sheet; (4) The final refined rubber sheet obtained above is discharged on a two-roll mill and left at room temperature for 4 hours; (5) The final refined rubber sheet after being left at room temperature for 4 hours is calendered into a rubber sheet of a set thickness by a calendering machine, and a calendering cord fabric of a corresponding thickness is added to form a capsule; (6) Place the capsule obtained in the above step into a mold, close the mold and vulcanize for 10-15 minutes at a vulcanization temperature of 150-170°C to obtain the desired rubber.

2. A method for preparing rubber for air spring bag skin according to claim 1, characterized in that The chloroprene rubber used in step (1) is DCR 40A chloroprene rubber; the epoxidized natural rubber is ENR 25 epoxidized natural rubber; and the styrene-butadiene rubber is SBR 1502 synthetic rubber.

3. The method for preparing rubber for air spring bag skin according to claim 1, characterized in that The magnesium oxide used in step (1) is high-activity magnesium oxide RS-180.

4. The method for preparing the rubber for the air spring bag skin according to claim 1, characterized in that The homogenizing agent used in step (1) is 40MSF uniform tackifier; the polyethylene wax is BN-200 polyethylene wax; and the processing aid is Haftolat / P processing aid.

5. The method for preparing rubber for air spring bag skin according to claim 1, characterized in that The antioxidant used in step (1) is a combination of OCTAMINE antioxidant and DTPD antioxidant.

6. The method for preparing rubber for air spring bag skin according to claim 1, characterized in that The reinforcing filler used in step (1) is a combination of VN3 white carbon black and N550 carbon black.

7. The method for preparing rubber for air spring bag skin according to claim 1, characterized in that The plasticizer used in step (1) is Mediaplast PM plasticizer.

8. The method for preparing rubber for air spring bag skin according to claim 1, characterized in that The antioxidant used in step (3) is antioxidant ZMTI.

9. The method for preparing rubber for air spring bag skin according to claim 1, characterized in that The adhesive used in step (3) is a combination of SCCTACK TR-1102 tackifying resin and SCCTACK ST-6000 phenolic tackifying resin.

10. The method for preparing rubber for air spring bladder as claimed in claim 1, characterized in that The vulcanizing agent used in step (3) is insoluble sulfur IS60-75; the accelerator is a combination of N-cyclohexyl-2-benzothiazole sulfenamide and diethyl diphenyl thiuram disulfide.

Citation Information

Patent Citations

  • Neoprene vibration reduction gasket material

    CN105482205A

  • Natural rubber-neoprene composition material as well as preparation method and application thereof

    CN108503903A

  • Novel outer-layer size used for automotive air spring and production method

    CN110343303A

  • Rubber composition as well as preparation method and application thereof

    CN112358667A

  • Automobile brake chamber rubber diaphragm sizing material composition and preparation method thereof

    CN115058069A